Analysis of Teritip Dam Utilization for Domestic Water Supply in Balikpapan - Kiamah Fathirizki Agsa Kamarati; Laode Muh Asdiq H Ramadhan; Herijanto Thamrin; Noorhamsyah; M. Masrudy; Sofyan Bulkis; M. Fadjery; Muhammad Zulfi; Ariusmiati; Shinta Sisilia Paurru (P2M Politeknik Pertanian Negeri Samarinda, 2023)
Balikpapan is a city in East Kalimantan, Indonesia, serving as a business and industrial center with the largest economy on the island of Kalimantan. The Teritip Dam has multiple purposes, including flood control and addressing the clean water crisis caused by a lack of raw water sources. The demand for clean water will continue to increase with population growth. This study aims to determine the contribution of the Teritip Dam in meeting the community's clean water needs through the Regional Drinking Water Company (PDAM) of Balikpapan. The study also seeks to provide input for potential contributions and conservation efforts. The analysis of domestic clean water demand involves evaluating the condition of clean water, identifying the supply and demand of clean water, analyzing population projections, and estimating the volume of clean water needed by the population. The study findings indicate that the Teritip reservoir provides a discharge of 8,891 m3/day, fulfilling only 14.3% of the clean water demand in Balikpapan. Therefore, implementing water resource conservation measures is crucial to meet the water demand in Balikpapan. These conservation activities include improving the supervision of water withdrawal and usage by considering conservation interests, raising public awareness about water issues, and controlling groundwater use for new drilling activities, particularly in critical groundwater areas.